2005
DOI: 10.1097/01.tp.0000174343.05590.9f
|View full text |Cite
|
Sign up to set email alerts
|

Acute Graft Pyelonephritis: A Potential Cause of Acute Rejection in Renal Transplant

Abstract: Acute graft pyelonephritis is a common complication in renal transplant recipients. The consequences of this complication on kidney allograft survival remain controversial. Bacterial infection is likely to activate the immune system, potentially leading to acute or chronic rejection. Here, we report for the first time two documented cases of acute rejection occurring shortly after acute graft pyelonephritis, suggesting that pyelonephritis can initiate acute rejection. The immunologic process leading to the all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 16 publications
1
51
0
4
Order By: Relevance
“…Indeed, Audard and associates have reported that among 9 kidney transplant patients with AGPN who had undergone a kidney biopsy less than 1 month after pyelonephritis, two (22%) had features of acute rejection. 10 Conversely, the results of a large series including 1387 consecutive primary kidney transplant patients did not support the hypothesis that AGPN may trigger an acute-rejection episode. 8 But no systematic kidney-allograft biopsies were performed.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Indeed, Audard and associates have reported that among 9 kidney transplant patients with AGPN who had undergone a kidney biopsy less than 1 month after pyelonephritis, two (22%) had features of acute rejection. 10 Conversely, the results of a large series including 1387 consecutive primary kidney transplant patients did not support the hypothesis that AGPN may trigger an acute-rejection episode. 8 But no systematic kidney-allograft biopsies were performed.…”
Section: Discussionmentioning
confidence: 79%
“…4 Finally, Audard and associates found that actuarial allograft survival was significantly lower in patients with AGPN compared with controls. 10 In summary, worse kidney function, acute rejection episodes, and tubulitis were observed in patients in whom eGFR did not return to its baseline values within 1 month after AGPN. Elevated interstitial infiltrate was associated with worse long-term kidney function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, increases in HSA escalate the risk of acute rejection (Locke et al 2009). Additionally, Audard et al (2005) reported two documented cases of acute rejection that occurred in the context of GPN, which strongly suggested that the immunological reaction was initiated by the infectious process. They suggested that bacterial products located within the graft regulate toll-like receptors, which (re)activate the alloreactive T-cells (Goldstein et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The findings from some studies have shown that GPN is associated with interstitial scarring in renal allografts (Dupont et al 2007) and that it can activate an alloimmune response to the donor organ and subsequently contribute to acute or chronic rejection (Audard et al 2005;Locke et al 2009). In a previous cohort study, the occurrence of early-onset GPN following kidney transplantation was significantly associated with increased rates of renal allograft loss (Giral et al 2002).…”
Section: Introductionmentioning
confidence: 99%